2022
DOI: 10.3389/fnagi.2022.880897
|View full text |Cite
|
Sign up to set email alerts
|

Novel Non-invasive Transcranial Electrical Stimulation for Parkinson’s Disease

Abstract: Conventional transcranial electrical stimulation (tES) is a non-invasive method to modulate brain activity and has been extensively used in the treatment of Parkinson’s disease (PD). Despite promising prospects, the efficacy of conventional tES in PD treatment is highly variable across different studies. Therefore, many have tried to optimize tES for an improved therapeutic efficacy by developing novel tES intervention strategies. Until now, these novel clinical interventions have not been discussed or reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The main difference between the effects of rTMS and tDCS is that rTMS can trigger an action potential and tDCS can only modulate resting membrane potential and change the probability of the action potential occurrence (Nitsche et al 2008). Thus, tDCS affects active neurons and is usually combined with behavioral training for more pronounced and long-term effects (Ni et al 2022). In clinical practice, the gold standard for treatment of HD is currently the LSVT (Yuan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main difference between the effects of rTMS and tDCS is that rTMS can trigger an action potential and tDCS can only modulate resting membrane potential and change the probability of the action potential occurrence (Nitsche et al 2008). Thus, tDCS affects active neurons and is usually combined with behavioral training for more pronounced and long-term effects (Ni et al 2022). In clinical practice, the gold standard for treatment of HD is currently the LSVT (Yuan et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve our goal, we chose transcranial direct current stimulation (tDCS) that can be used remotely by patients at home together with a concurrent Lee Silverman Voice Treatment (LSVT), i.e., the best documented therapy for symptoms of HD in PD (Yuan et al 2020). In PD patients, tDCS and other modes of temporal electrical stimulation (tES) have mostly been used to modulate gait speed, freezing of gait, limb bradykinesia, attention and executive functions, and brain excitability (Ni et al 2022). Studies also provided evidence that homebased tDCS treatment is feasible and safe for PD patients (Dobbs et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported improvements in motor symptoms, tremors, and gait following TES with PD [60,131]. One type of TES studied in PD is tDCS, which involves the application of a weak electrical current to the scalp to modulate cortical excitability.…”
Section: Tes In Pdmentioning
confidence: 99%